2021
DOI: 10.1186/s12889-021-11584-0
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion interventions for African Americans delivered in U.S. barbershops and hair salons- a systematic review

Abstract: Background African American adults suffer disproportionately from obesity-related chronic diseases, particularly at younger ages. In order to close the gap in these health disparities, efforts to develop and test culturally appropriate interventions are critical. Methods A PRISMA-guided systematic review was conducted to identify and critically evaluate health promotion interventions for African Americans delivered in barbershops and hair salons. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…In a systematic review, interventions that were led or supported by a barber or hair stylist had a positive impact on both intervention effectiveness and feasibility. 13 When barbers and stylists were trained on intervention content and delivery, there were high levels of implementation, satisfaction with the intervention by clients, and intention to continue with the intervention beyond the study. 13 Studies that linked intervention delivery to a clinical partner reported significant positive results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review, interventions that were led or supported by a barber or hair stylist had a positive impact on both intervention effectiveness and feasibility. 13 When barbers and stylists were trained on intervention content and delivery, there were high levels of implementation, satisfaction with the intervention by clients, and intention to continue with the intervention beyond the study. 13 Studies that linked intervention delivery to a clinical partner reported significant positive results.…”
Section: Discussionmentioning
confidence: 99%
“… 13 When barbers and stylists were trained on intervention content and delivery, there were high levels of implementation, satisfaction with the intervention by clients, and intention to continue with the intervention beyond the study. 13 Studies that linked intervention delivery to a clinical partner reported significant positive results. 13 In another study, barbers who went through training to deliver information on prostate cancer screening to their clients, had significantly higher levels of prostate cancer knowledge post-training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other health promotion campaigns are using barbershops and hair salons as potential opportunities for intervention. While some evaluation studies for education on hypertension and diabetes show promising results, more research is needed to evaluate the effectiveness of utilizing these locations for community-level interventions [ 47 ]. Specific interventions and studies are needed to address community-level education on trauma and anxiety-related symptoms to improve recognition and referrals for care in Black communities.…”
Section: Structural Barriers Associated With the Intersection Of Traumatic Stress And Gun Violence: A Case Example Of New Orleansmentioning
confidence: 99%
“…Various initiatives have been influenced by the ‘barbershop model’ of health promotion that emerged in the 1980s to address health problems in African-American communities, for whom barbershops have historically provided a safe gathering place with important social and cultural functions. 14 Key components of the barbershop model have included training barbers to improve health literacy and offering guidance on how to initiate client referrals to professional healthcare providers. However, mental health outcome data have been scarcely reported and the applicability to other populations and contexts is uncertain, despite international interest and examples of public funding.…”
mentioning
confidence: 99%